Analysis of Farmer and Forestry Cooperation in Forest Agriculture Management: An Islamic Economic Perspective - Mariyah Ulfah; Siti Alfiyah (al-Afkar, Journal For Islamic Studies, 2025)
This study examines the cooperation mechanism between farmers and Perhutani in forest agricultural management in Ngasem District, Bojonegoro Regency, from the perspective of Islamic economics. The licensing process is conducted through the Forest Village Community Institution (Lembaga Masyarakat Desa Hutan or LMDH) under a Cooperation Agreement Scheme (Perjanjian Kerja Sama or PKS). Community members interested in managing forest land submit their applications through village officials, after which Perhutani grants approval and provides training programs on forest agricultural management. The profit-sharing scheme stipulates that 10% of the harvest yield is allocated to Perhutani. This research employs a qualitative method with a field research approach, utilizing data collection techniques such as observation, interviews, and documentation. The findings indicate that, from an Islamic economic perspective, this cooperation aligns with the mukhābarah contract, where Perhutani acts as the land provider, and LMDH is responsible for seeds, production costs, and land management until harvest. The profit-sharing model is considered consistent with the principles of justice in Islam, as the rights and obligations of each party are clearly defined. This study underscores the importance of contractual clarity in ensuring fair and sustainable cooperation.